2013
DOI: 10.1007/s10198-013-0541-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ageing on health care expenditures: a study of steepening

Abstract: Some researchers claim that health care expenditures for older people are growing faster than for the rest of the population. This process is referred to as steepening. The aim of this paper is to test steepening, applying new data and revised methods. Furthermore, we explain the connection between the terms red herring hypothesis, i.e., that time to death and not age per se drives the health care expenditures, and steepening. We also present the mechanisms that may induce steepening, as presented in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 23 publications
0
28
0
2
Order By: Relevance
“…The impact of an ageing population on healthcare expenditures has been widely discussed over the past three decades. [1][2][3][4][5][6][7][8][9][10][11][12] While some studies have suggested that rapid growth in the older adult population (defined as ages 65 and above) is a significant cost-driver for healthcare services, through mechanisms such as increased utilisation due to longer lifespan, [1][2][3]6,8,10 some have argued that the ultimate effect on healthcare expenditure is mild. 5,7,9,11,12 In either case, the magnitude and rate of the increases in the demand for healthcare services relating to age-associated medical conditions has left many countries unprepared.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of an ageing population on healthcare expenditures has been widely discussed over the past three decades. [1][2][3][4][5][6][7][8][9][10][11][12] While some studies have suggested that rapid growth in the older adult population (defined as ages 65 and above) is a significant cost-driver for healthcare services, through mechanisms such as increased utilisation due to longer lifespan, [1][2][3]6,8,10 some have argued that the ultimate effect on healthcare expenditure is mild. 5,7,9,11,12 In either case, the magnitude and rate of the increases in the demand for healthcare services relating to age-associated medical conditions has left many countries unprepared.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the steepening hypothesis, Felder and Werblow have argued that the steepening effect is real, but weaker than previously believed [8]. More recently, Gregersen reported some evidence of steepening in Norwegian hospital data [9], but it was not as strong as indicated by Buchner and Wasem. It should be noted that the strength of the empirical conclusions also depends on whether the definition of health expenditure includes long-term nursing care.…”
mentioning
confidence: 88%
“…This research has detected income elasticity to be above unity, implying that the share of health expenditure of GDP increases with the rise in per capita income. However, other papers like Smith, Newhouse, and Freeland (2009) and Follette andSheiner (2008 and2014), declare that household-level estimates may not be predicted and illustrated by macroeconomic data. Therefore, they propose that adopting microeconomic data is more useful for estimating income elasticity.…”
mentioning
confidence: 99%
“…Similarly, Amy Finkelstein (2007 and showed that analyzing the effect of medical service prices is not accurate without considering the role of insurance. Dalgaard and Strulik (2012, 2014 have investigated the role of age in healthcare expenditure and find it to be one of the most important effecting variables of healthcare expenditure. Wagstaff's (1986) effort for identifying effecting variables of demand for health and healthcare expenditure finds family income, age of family and family size as the most important variables to consider.…”
mentioning
confidence: 99%
See 1 more Smart Citation